Using PaCO2 values to grade obesity-hypoventilation syndrome severity: a retrospective study - Damiani, Mario Francesco; Falcone, Vito Antonio; Carratù, Pierluigi; Scoditti, Cristina; Bega, Elioda; Dragonieri, Silvano; Scoditti, Alfredo; Resta, Onofrio (Multidisciplinary Respiratory Medicine, 2017)
Background Hypersensitivity pneumonitis (HP) is a common diffuse parenchymal lung disease in Egypt which can be difficult to recognize due to the dynamic symptoms & associated environmental factors. Methods Forty-three Egyptian patients were enrolled in this study, presenting with dyspnea and cough, predominant ground-glass opacity (GGO) in high-resolution computed tomography (HRCT) where lung biopsy was needed to establish the diagnosis. Results The age range was 15 to 60 years. Females represented 90.7% (39 patients) while 9.3% (4 patients) of our patients were males. History of contact with birds was detected in 9 (20.9%) patients. Most of our patients (60.5%) didn’t have exposure history, and only 8 patients (18.6%) were living in geographic areas in Egypt that are known for the exposure to environmental etiologic factors (cane sugar exhaust fumes). The most common HRCT pattern was GGO with mosaic parenchyma in 18 patients (41.86%), followed by GGO with centrilobular nodules in 9 patients (20.93%), then isolated diffuse GGO in 5 patients (11.62%), GGO with traction bronchiectasis in 4 patients (9.3%), GGO with consolidation in 3 patients (6.97%), GGO with reticulations in 2 patients (4.65%), and GGO with cysts in 2 patients (4.65%). The most common histologic finding was isolated multinucleated giant cells in 38 patients (88.3%) commonly found in airspaces (24 patients) and less commonly in the interstitium (14 patients), followed by interstitial pneumonia and cellular bronchiolitis in 36 patients (83.7% each), interstitial ill-formed non-necrotizing granulomas in 12 patients (27.9%), fibrosis in 10 patients (23.2%), and organizing pneumonia pattern in 4 patients (9.3%). Conclusion. The diagnosis of HP presenting with predominant GGO pattern in HRCT requires a close interaction among clinicians, radiologists, and pathologists. Some environmental and household factors may be underestimated as etiologic factors. Further environmental and genetic studies are needed especially in patients with negative exposure history.